In vitro activity of hybrid lavender essential oils against multidrug resistant strains of Pseudomonas aeruginosa - Matthew Donadu; Donatella Usai; Antonio Pinna; Tiziana Porcu; Vittorio Mazzarello; Maura Fiamma; Mauro Marchetti; Sara Cannas; Giovanni Delogu; Stefania Zanetti; Paola Molicotti (Journal of Infection in Developing Countries)
Introduction: Lavender is an evergreen shrub native to Northern Africa and other mountainous Mediterranean regions. It grows throughout Southern Europe, the United States, and Australia. Lavender essential oil has been used since ancient times and is known for its anti-inflammatory, antidepressant, antiseptic, antifungal and antimicrobial properties.